Getting ahead : three steps to take your career to the next level - Garfinkle, Joel A. (John Wiley & Sons, 2011)
A leading executive coach pinpoints three vital traits necessary to advance your career. What makes one person more successful than another? The answer: leveraging and applying perception, visibility, and influence better than anyone else. While some people leave the fate of their careers in someone else's hands, others determine their future using these three critical skills. In Getting Ahead, one of the top 50 executive coaches in the United States, Joel Garfinkle reveals his signature PVI model-Perception, Visibility, and Influence. Through practical advice, specific exercises, and action-oriented tips, readers will learn how to create the right image, increase their profile across the organization and among higher levels of management, and exert influence by driving change and inspiring people. Learn the key skills, effective tools, and tactical approaches that you can implement immediately in your current work situation to become an invaluable resource for the company. For more than two decades, Joel Garfinkle has worked closely with thousands of executives, senior managers, directors, and employees at the world's leading companies, and has authored 300 articles on leadership. Offers detailed guidance on how to increase exposure, boost visibility, enhance perceived value for your organization, and ultimately achieve career advancement. Explains how to get your name circulating among higher levels of management so others know you, see your results, and acknowledge the impact you bring to the company. Eliminate the roadblocks that keep you from advancing. Getting Ahead will put you ahead of the competition to become a known, valued, and desired commodity at your company.